2014
DOI: 10.1016/j.biopsych.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence for β2 Nicotinic Acetylcholine Receptor Subunit Upregulation in Smokers as Compared With Nonsmokers With Schizophrenia

Abstract: Background: Schizophrenia is associated with very high rates of tobacco smoking. The latter may be related to an attempt to “self-medicate” symptoms and/or to alterations in function of high affinity nicotinic acetylcholine receptors (β2*-nAChRs). Methods: Smoking and nonsmoking subjects with schizophrenia (n=31) and age-, smoking- and sex-matched comparison subjects (n=31) participated in one [123I]5-IA-85380 single photon emission computed tomography (SPECT) scan to quantify β2*-nAChR availability. Psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 65 publications
10
42
1
Order By: Relevance
“…On the other hand, autoradiographic studies indicated an absence of the upregulation of the high-affinity α4β2 nAChRs in the cortex, striatum and hippocampus of smokers with schizophrenia, which is typically seen in normal smokers (Breese et al, 2000; Durany et al, 2000). Recent human neuroimaging studies employing positron emission tomography (PET) technique also show reduced β2*-nAChR availability in smokers with schizophrenia as compared to smokers without schizophrenia (Brašić et al, 2012) but higher upregulation in comparison to non-smoker schizophrenia patients (Esterlis et al, 2014). These findings suggested that either desensitization or turnover of α4β2 nAChRs is abnormal in subjects with schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, autoradiographic studies indicated an absence of the upregulation of the high-affinity α4β2 nAChRs in the cortex, striatum and hippocampus of smokers with schizophrenia, which is typically seen in normal smokers (Breese et al, 2000; Durany et al, 2000). Recent human neuroimaging studies employing positron emission tomography (PET) technique also show reduced β2*-nAChR availability in smokers with schizophrenia as compared to smokers without schizophrenia (Brašić et al, 2012) but higher upregulation in comparison to non-smoker schizophrenia patients (Esterlis et al, 2014). These findings suggested that either desensitization or turnover of α4β2 nAChRs is abnormal in subjects with schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…Recent human PET/SPECT imaging studies that employed a β2 nAChR agonist radiotracer [123I]5-IA-85380 showed not only lower α4β2 nAChR availability in smokers with schizophrenia as compared to normal smokers but also a negative correlation between the receptor availability and negative symptoms (D’Souza et al, 2012; Esterlis et al, 2014). Smoking cigarettes high in nicotine content reduced negative symptoms of schizophrenia more than denicotinized cigarettes (Smith et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…α7 nAChR subunit polymorphisms are associated with severity of P50 auditory deficits that are associated with impaired attention in people with schizophrenia (Freedman et al 1997), an impairment that is partially reversed with α7 nAChR partial agonists (Olincy et al 2006). Recent in vivo evidence indicates that tobacco smoking is associated with upregulation of high affinity α4β2 nAChRs in the striatum and cortex in smokers with schizophrenia compared to non-smokers with schizophrenia, such that receptor levels in smokers with schizophrenia are not different from non-smoking healthy volunteers (Esterlis et al, 2013). nAChR availability was inversely associated with negative symptoms and positively correlated with cognitive performance in smokers with schizophrenia (Esterlis, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vivo evidence indicates that tobacco smoking is associated with upregulation of high affinity α4β2 nAChRs in the striatum and cortex in smokers with schizophrenia compared to non-smokers with schizophrenia, such that receptor levels in smokers with schizophrenia are not different from non-smoking healthy volunteers (Esterlis et al, 2013). nAChR availability was inversely associated with negative symptoms and positively correlated with cognitive performance in smokers with schizophrenia (Esterlis, et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…47 These receptors have been shown to be upregulated among smokers, both in healthy samples and in patients with schizophrenia. [48][49][50] In animal models, prolonged exposure to nicotine in early development, adolescence and, to some extent, in adulthood has been shown to lead to desensitization and lasting deleterious effects on cholinergic synaptic transmission. 51,52 Although it is possible this could result in cortical thinning, other neurotoxic effects, such as oxidative stress or apoptosis, cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%